Kedudukan Negara Sebagai Kreditur Preferen dalam Piutang Pajak dalam Kasus Kepailitan - Shafira Hijriya (Faculty of Law, Andalas University, 2017)
State has preference right in obtaining repayment of the insolvent company. The position of secured creditors are not affected by the bankruptcy. This means that creditors can exercise their rights as if no bankruptcy occurred, so it will generate inequality among creditors tax receivables (state) with secured creditors. After the bankruptcy decision handed down, the organization of the bankrupt debtor assets will switch to a curator under the supervision of the supervisory judge. Curator duty to sell or transfer the bankruptcy estate to the extent necessary to cover the cost of bankruptcy. Sometimes the sale of the bankruptcy estate is insufficient to pay the debt debtor bankruptcy, including tax. The purpose of this research article was to compare the tax receivable creditor position with secured creditor and other creditors in case of bankruptcy and to know the completion of the allocation of the bankruptcy estate if it is not sufficient to pay the tax debt and other debts under the Bankruptcy and Suspension of Payment Act and the Taxation General Provisions Act. The results of this research article showed that, first, the position of the state as compared to the secured creditor and other creditors in case of bankruptcy under the Bankruptcy and Suspension of Payment Act and the Taxation General Provisions Act is at a higher position than the position of the secured creditor and other creditors because of preference’s rights that take precedence in the repayment of debt of debtor. Second, the completion of the allocation of the bankruptcy estate if it is not sufficient to pay the tax bill and other bills is to give priority to pay off the tax bill is divided in proportion to the ratio of the amount of the bill, respectively, although the rest of the tax bill has not been paid off, is not considered the responsibility of the curator again because the bankruptcy has ended.